Induced mutations in cowpea, Vigna unguiculata (Leguminosae) - Odeigah, PGO (1998)
Two cowpea (Vigna unguiculata L. Walp) vatietiés, IT84E-124 and Vita 7 of the Intemational Inslitute of Tropícal Agriculture, Ibadan, were exposed lo Varying doses of chernieal and physical mutagens. Optimum doses of 10mM EMS for 6hr andO.l rnM aod 1.OrnM NaN3 for 2hr, determíned frorn seedling growth tests and lOOR and 2ooR,garnma radiaticins were applied 10 2000 seed samples of each ,genotype. Sereening of the M2 generation revealed, lhat the rnutagenic treatrnents indueed rnorphological, physiologie;¡land biochemicalchanges in the genotypes: A spectrum of rnutations which included variants.wilh respect t()anthocyanin pigmentatiCln, ¡ellf morphology, maturity date, male sterility and insec.tpestresístancequalitieswere observect; Unes withsignificant increases in yield parameters such as .rtumber or seeds pefpod, pedimcles per plant, 100 seed weight and seed storage proteinswere selected.